Digitalisasi Akuntansi Persediaan Berbasis Sistem Informasi pada UMKM: Studi Kualitatif Transformasi Digital Bisnis - Fitrah Sakinah; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the digitalization of inventory accounting based on information systems within MSMEs in the context of digital business transformation through a qualitative literature-based approach. The study focuses on understanding how digital accounting systems reshape inventory management, operational efficiency, internal control mechanisms, and managerial decision-making processes in small and medium enterprises. The analysis was conducted using content analysis and thematic interpretation of academic literature related to accounting information systems, inventory management, digital transformation, and MSME sustainability. The findings indicate that digital-based accounting systems improve the accuracy of inventory records, accelerate information processing, strengthen internal control, and enhance data integration across business activities through real-time monitoring mechanisms. The study also reveals that digital transformation in MSMEs is influenced by organizational readiness, digital literacy, infrastructure availability, and the adaptability of human resources toward technological change. Despite various implementation challenges, digitalization contributes significantly to business sustainability and competitiveness by supporting more adaptive, transparent, and data-driven management practices in the digital economy era.